Effects of Novel Photosynthetic Inhibitor [CuL2]Br2 Complex on Photosystem II Activity in Spinach - Sergey K. Zharmukhamedov; Mehriban S. Shabanova; Margarita V. Rodionova; Irada M. Huseynova; Mehmet Sayım Karacan; Nurcan Karacan; Kübra Begüm Aşık; Vladimir D. Kreslavski; Saleh Alwasel; Suleyman I. Allakhverdiev (Cells, 2022)
The effects of the novel [CuL2]Br2 complex (L = bis{4H-1,3,5-triazino [2,1-b]benzothiazole-2-amine,4-(2-imidazole)}copper(II) bromide complex) on the photosystem II (PSII) activity of PSII membranes isolated from spinach were studied. The absence of photosynthetic oxygen evolution by PSII membranes without artificial electron acceptors, but in the presence of [CuL2]Br2, has shown that it is not able to act as a PSII electron acceptor. In the presence of artificial electron acceptors, [CuL2]Br2 inhibits photosynthetic oxygen evolution. [CuL2]Br2 also suppresses the photoinduced changes of the PSII chlorophyll fluorescence yield (FV) related to the photoreduction of the primary quinone electron acceptor, QA. The inhibition of both characteristic PSII reactions depends on [CuL2]Br2 concentration. At all studied concentrations of [CuL2]Br2, the decrease in the FM level occurs exclusively due to a decrease in Fv. [CuL2]Br2 causes neither changes in the F0 level nor the retardation of the photoinduced rise in FM, which characterizes the efficiency of the electron supply from the donor-side components to QA through the PSII reaction center (RC). Artificial electron donors (sodium ascorbate, DPC, Mn2+) do not cancel the inhibitory effect of [CuL2]Br2. The dependences of the inhibitory efficiency of the studied reactions of PSII on [CuL2]Br2 complex concentration practically coincide. The inhibition constant Ki is about 16 µM, and logKi is 4.8. As [CuL2]Br2 does not change the aromatic amino acids’ intrinsic fluorescence of the PSII protein components, it can be proposed that [CuL2]Br2 has no significant effect on the native state of PSII proteins. The results obtained in the present study are compared to the literature data concerning the inhibitory effects of PSII Cu(II) aqua ions and Cu(II)-organic complexes.